One-pot Synthesis of Pt Catalysts Supported on Al-modified TiO2 - Rebecca E. Olsen; Calvin H. Bartholomew; David B. Enfield; Brian F. Woodfield (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2014)
A facile, industrially viable, one-pot synthesis of 0.5-8 wt% Pt supported on 22 mol% Al-modified ana-tase with high surface area and thermal stability is presented. Four pathways were studied to deter-mine the effects of support properties on catalyst dispersion, and the highest dispersions were observed for high surface area materials containing 5-coordinate anatase. Systematic study of preparation vari-ables shows that low drying temperatures, slow calcination ramp rates, and slow reduction ramp rates further increased Pt dispersion and resulted in a more uniform Pt size distribution. Pt dispersions as high as 54% have been obtained using the one-pot method and 59% for Pt catalysts synthesized by dry impregnation. Statistically designed studies are needed to more completely determine the effects of synthesis variables and to optimize the dispersion and reduction of Pt supported on Al-modified ana-tase. Results presented in this paper show that this one-pot method and dry impregnation method us-ing our Al-modified anatase support are promising syntheses of highly dispersed Pt supported on stabi-lized titania. Our results demonstrate that the alumina-stabilized anatase support is superior to other anatase supports for (1) obtaining high Pt dispersions, i.e. more efficiently utilizing this expensive pre-cious metal, and (2) processes in which thermal stability is important due to its constant phase and pore structures at high temperatures. © 2014 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)